To solve this expression, we can start by simplifying the terms individually.
First, let's simplify -15 + 4/5:
-15 + 4/5 = -75/5 + 4/5 = (-75 + 4)/5 = -71/5
Next, let's simplify 15e-10:
15e-10 = 15 * (1/e^10) = 15/e^10
Finally, let's simplify -10e:
-10e
Now we can substitute these simplified terms back into the original expression:
-71/5 + 15/e^10 - 10e
Since we don't have any common denominators, it would be difficult to simplify further without more information. Therefore, none of the provided answer choices can accurately represent the value of this expression.
-15+4/5 (15e-10)-10e
use these answers
2e+23
2e-23
-2e+23
-2e-24
1 answer